Carcass characteristics of intensively fed finisher lambs maintained on varying plane of nutrition in pre -weaning phase - KARIM, S A; SANTRA, A; SEN, A R; SHARMA, V K (The Indian Journal of Animal Sciences, 2014)
The impact of pre weaning plane of nutrition (high, G1; medium, G2; low, G3) on post-weaning growth and carcass characteristics of finisher lambs was evaluated. The weaning weights were 14.3, 13.0 and 14.8 kg in GI, G2 and G3, respectively, while the finishing weight was higher (P< 0.01) in the G3 (24.8 kg), maintained on low plane of nutrition in pre weaning phase, than G1 (21.9 kg) or G2 (21.0 kg). The pre slaughter weight, empty live weight, hot carcass weight with kidney and kidney fat and hot carcass weight with edible offal were higher (P